2016
DOI: 10.1016/j.atherosclerosis.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

PKCε mediates resistin-induced NADPH oxidase activation and inflammation leading to smooth muscle cell dysfunction and intimal hyperplasia

Abstract: Backgrund and aims Resistin has been implicated in cardiovascular disease and poor interventional cardiovascular outcomes. Previous studies by our group demonstrated resistin promoted vascular smooth muscle cell (VSMC) migration through protein kinase C epsilon (PKCε) pathways, while few others showed that resistin induced reactive oxygen species (ROS) generation in various cell types. In this study, we aim to systemically examine the functional role of resistin at the cellular and tissue levels as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…16, 24 In this study, we observed that PKCε is a key mediator of resistin signaling for macrophage activation, suggesting that inhibiting PKCε has anti-inflammatory properties. Our study is in line with previous findings proposing that TLR4 participates in resistin-associated activity in macrophages.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…16, 24 In this study, we observed that PKCε is a key mediator of resistin signaling for macrophage activation, suggesting that inhibiting PKCε has anti-inflammatory properties. Our study is in line with previous findings proposing that TLR4 participates in resistin-associated activity in macrophages.…”
Section: Discussionmentioning
confidence: 64%
“…We recently showed that resistin increased ROS production, NADPH oxidase (Nox) activity, and inflammatory cytokine secretion in VSMCs. 16 We speculate that ROS production and Nox activity may also contribute to this pathway, and play important roles in the overall inflammatory cascades that are activated by resistin.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Resistin, an adipokine produced by perivascular adipose tissue, contributes to intimal hyperplasia and atherosclerosis (Nosalski and Guzik, ). Resistin induces the proliferation and migration of VSMCs via the ERK1/2 or PI3K‐Akt (Calabro et al ., ) and integrin α5β1‐FAK/paxillin‐Rac1 (Jiang et al ., ) or PKC (Raghuraman et al ., ) signalling pathways respectively. Moreover, resistin leads to endothelial dysfunction as shown by the up‐regulation of VCAM‐1 and ICAM‐1 expression, as well as the increased secretion of endothelin‐1 and CCL2 by ECs (Verma et al ., ; Jamaluddin et al ., ).…”
Section: The Interaction Between Vascular Injury and Injury To Other mentioning
confidence: 99%
“…[29] The current view is inclined that SMCs migrated from the middle membrane of blood vessel walls participates in the early stage of IH. [30][31][32] Another view is that the physiological phenotype of SMCs is contractile, while the pathological phenotype of SMCs is synthetic, and the change of SMCs from contractile to synthetic phenotype leads to IH happen. [33] Recent finding showed that multipotent vascular stem cells also contribute to intimal hyperplasia by differentiating into synthetic SMCs, [34] which further challenged the general dogma about de-differentiation of SMCs from the contractile to the synthetic phenotype.…”
Section: Surface Functionalization For Anti-hyperplasiamentioning
confidence: 99%